Primary Cardiac Sarcoma: 25-Year Cleveland Clinic Experience. (December 2016) - Randhawa, Jaskirat S.; Budd, George T.; Randhawa, Mandeep; Ahluwalia, Manmeet; Jia, Xuefei; Daw, Hamed; Spiro, Timothy; Haddad, Abdo
Abstract : Background: Cardiac sarcomas are rare and have a poor prognosis. The median overall survival remains dismal and has been reported ranging from 6 months to a few years. Primary cardiac sarcoma is the most common malignant tumor comprising approximately 95% of all malignant tumors of the heart. Methods: We conducted a retrospective chart review in a single institution of patients diagnosed between March 1988 and April 2013. A total of 42 patients were identified. The following variables were studied: age at diagnosis, year of diagnosis, sex, stage, site of tumor involvement, tumor histology, grade, treatment modality, type of chemotherapy, and survival outcome. The overall median follow-up time was 49.5 months. Results: The most common histologic type was angiosarcoma. Overall estimated median survival (EMS) was 25 months. Tumors involving the left side of the heart and pericardium demonstrated better survival. Patients who received multimodality treatment (any combination of surgery, radiation therapy, and chemotherapy) had an EMS of 36.5 months compared with 14.1 months for patients treated with surgery, radiation therapy, or chemotherapy only ( P =0.05). Conclusions: Cardiac sarcoma is a lethal tumor with an EMS of 25 months. The tumor histology could be a possible predictor of better survival. Although selection bias may have been present, multimodality therapy (surgery, radiation therapy, and chemotherapy) was associated with improved survival.